The Use of the Beautiful Novel by Eka Kurniawan as a Teaching Material: An Analysis Based on Grounded Theory - Rahmayati, Nisa Dwi; Saharudin, Saharudin; Sirullhaq, Muhammad; Musaddat, Syaiful (Journal of Social Science and Education Research, 2025)
The Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) initiated by the Education Standards, Curriculum, and Assessment Agency (BSKAP) issued a policy called "Literature Enters the Curriculum". However, not long after this program was issued, several pros and cons have emerged regarding this policy, one of which is the use of the novel Cantik Itu Luka as a learning material in high school. This study will describe how the use of the novel Cantik Itu Luka as a learning material uses Grounded Theory from Strauss & Cobin and describes its advantages and disadvantages. In collecting data, this study used a reading and note-taking technique with an instrument in the form of a data table as an aid. The use of the novel Cantik Itu Luka by Eka Kurniawan as a teaching material can be done with a comprehensive approach, utilizing major themes to teach various concepts in the fields of literature, history, psychology, social, and gender. The novel Cantik itu Luka as a teaching material has advantages, namely: The story is deep and complex, there is unique realism and magic, raises relevant social issues, character and moral value approaches, and can be used as multidisciplinary and critical material. In addition to its advantages, this novel also has disadvantages, including: Heavy, controversial and challenging language and content, a long story and complex plot, limitations in developing reader focus, and a lack of positive representation in female characters.